Kemampuan Pemahaman Konsep Siswa dengan Pembelajaran Guided Discovery Learning - Ramananda, Putri Cantika; Arifin, Sujinal; Liana, Liana (SJME (Supremum Journal of Mathematics Education), 2024)
The aim of this research is to describe students' ability to understand concepts using the guided discovery learning model in learning statistics material. The method used in this research is quasi-experimental with a one-shot case study design. The data collection technique used consisted of a test of the ability to understand mathematical concepts in the form of a description of 7 test questions and interviews. The ability to understand concepts can be seen from the analysis of students' answers to test questions given to 28 students whose research subjects were class VIII students at SMP Negeri 46 Palembang. From the results of this test, interviews were then conducted with 4 students who received ability scores in three categories of low, medium and high. The results of this research show that more than 20 students have met the indicators of ability to understand concepts with an average answer of 80% -93% with an average score of "83.88", a very good assessment criterion.